A deep and handcrafted features‐based framework for diagnosis of COVID‐19 from chest x‐ray images. (19th November 2021) - Bozkurt, Ferhat
Abstract: Automatic early diagnosis of COVID‐19 with computer‐aided tools is crucial for disease treatment and control. Radiology images of COVID‐19 and other lung diseases like bacterial pneumonia, viral pneumonia have common features. Thus, this similarity makes it difficult for radiologists to detect COVID‐19 cases. A reliable method for classifying non‐COVID‐19 and COVID‐19 chest x‐ray images could be useful to reduce triage process and diagnose. In this study, we develop an original framework (HANDEFU) that supports handcrafted, deep, and fusion‐based feature extraction techniques for feature engineering. The user interactively builds any model by selecting feature extraction technique and classification method through the framework. Any feature extraction technique and model could then be added dynamically to the library of software at a later time upon request. The novelty of this study is that image preprocessing and diverse feature extraction and classification techniques are assembled under an original framework. In this study, this framework is utilized for diagnosing COVID‐19 from chest x‐ray images on an open‐access dataset. All of the experimental results and performance evaluations on this dataset are performed with this software. In experimental studies, COVID‐19 prediction is performed by 27 different models through software. The superior performance with accuracy of 99.36% is obtained by LBP+SVM model.